Students’ Attitudes on Gamification in English Reading Classes: The Use of Kahoot! - Suparmi, Suparmi -; Susanto, Alifarga Kresnayoga (Journal of English for Academic and Specific Purposes (JEASP), 2025)
This study explores students’ reflective attitudes of using Kahoot! in their reading classes, with a focus on its effects on engagement, motivation, and reading comprehension. A qualitative research design was used to collect data from ten students using semi-structured interviews and classroom observations. The findings show that Kahoot! significantly increasing student engagement by making learning of reading interactive and enjoyable. Students also reported increased motivation and a more positive attitude toward reading, largely due to the game-based nature of the platform. Moreover, Kahoot! was also found to enhance reading comprehension since it assisted students focus on the important points in the text through repeated exposure and immediate feedback. The study also highlighted how Kahoot!’s encouragement of friendly competition and peer interaction contributed to a more dynamic and collaborative learning environment. Nevertheless, technical challenges were identified as a limitation, negatively impacting the platform’s overall effectiveness, particularly those pertaining to internet connectivity. These findings indicate that while Kahoot! provides significant educational benefits, its effective implementation in the classrooms depends on a stable technical infrastructure. The study enhances understanding of the role of game-based learning tools in education and suggests the need for further investigation into students’ long-term effects on academic performance.